Instagram Performance Analysis of Micro, Small, and Medium Enterprises: A Case Study in the Fashion Sector - Maulana, Ahmad Saufi; Agung Andhika F.; Balqies Savina; F.ti Ayyu Sayyidul L.; Fachrul Kurniawan (Association for Scientific Computing Electrical and Engineering, 2022)
People nowadays rely on social media, which has become a necessity in their everyday lives. With 13 % of internet users, Instagram is currently the largest social network. This is an opportunity for Micro, Small, and Medium Enterprise (MSME) owners who target Instagram users as their market. This paper analyses the performance of Instagram in selling MSME fashion products, especially thrift shops. Based on the data, followers, likes, and comments do not influence the item's sale. The research finds some factors that can increase the sale of goods on Instagram, such as ads, paid promotions, endorsements, events, and giveaways. Furthermore, The results deliver strategies to improve sales through the Instagram platform